Development of a speciesspecific probe for detection of Serratia entomophila in soil - Hurst, M.R.H.; Young, S.D.; O'Callaghan, M. (New Zealand Plant Protection, 2008)
Strains of the bacteria Serratia entomophila and S proteamaculans cause amber disease in the grass grub Costelytra zealandica (Coleoptera Scarabaeidae) an important pasture pest in New Zealand Strains of both Serratia species occur naturally in New Zealand pasture soils Serratia entomophila has been developed as a commercial biological control agent bioshield The persistence of the applied strain in soil is currently measured by enumeration of bacterial colonies on Serratiaselective agar and subsequent biochemical tests are carried out to differentiate between the two Serratia species on the basis of their ability to utilise itaconate as a sole carbon source A speciesspecific DNA probe has been developed as an alternative to these laborious biochemical tests Tests against a range of Serratia species in colony dot blots showed the probe could be used to differentiate between S entomophila and S protemaculans recovered from treated soil when assessing persistence of bioshield inoculum and efficacy of the product in the field